International Conference of Young Scientists "Advances in Botany and Ecology" (June 03–July 29, 2016, Kherson, Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2016)
International Conference of Young Scientists "Advances in Botany and Ecology" (June 03–July 29, 2016, Kherson, Ukraine)